Students' understanding of equal and equality symbols in mathematics - Izzatul Nabila, Sarbini (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study aims to identify the Fonn 1 students' understanding of equal and equality symbols. The specific objectives are to investigate whether the fonn 1 students have problem in solving questions involving equations of one side such as "23+24 = 47"; to investigate whether the fonn 1 students have problem in solving. questions involving equations of both sides such as "23+24-16 = _+25-13"; to investigate whether the form 1 students have problem in translating the mathematic sentence into symbols and vice versa and to find out the definition of equal and equality symbols from the students view. In this study, instrument were taken from Oksuz,(2007) and Knuth et al, (2006). The instrument consists of 12 questions and the questions were divided into five sections. The instrument includes various types of questions including true/false question, multiple choice questions, fill out question, and open question sentences. In this study, the participants were 15 Fonn 1 students from the secondary school located in Petrajaya, Kuching. During the data collection, the students were given 30 minutes to complete the exercise. Then, the data were analyzed and the results were discussed. From the findings it is found that students do not have any problem in solving the equation with none rule violation which means the equation is on the left side while the equal symbol is on the right side for example "4 + 6 = 10". However, the students have a slight problem when given questions that violate the rules where the equation is on the right side and the equal symbol is on the left side for example "9 = 5 + 4". Apart from that, this study also found that the students has problem in solving equation that appear on both sides. When given question such as "4 + 6 = [ ] + 2", the students think that lOis the answer for the unknowns. It shows that students think that the answer should come after the equal symbol. Moreover, the students were not able to write the correct equation to represent the given situation. Most of the students write an equation that shows their understanding in arithmetic and not in tenns of algebraic thinking. It is also found that none of the students were able to use the equal symbol to show the relationship between the equations. The students think that the symbol is a symbol to show the answer or to represent the answer and this might be the cause of their misconception in the exercise. Therefore, further research on investigating the reason of each misconception should be done. In addition, a research on finding the appropriate instructional strategies to solve this problem can be done in the future. This will improve the students understanding in learning mathematics.